Effects of multiple-dose esomeprazole and pantoprazole on diazepam pharmacokinetic profile and pharmacodynamic effects on cognitive and psychomotor function in healthy volunteers - Drewelow, Bernd; Schaffler, Klaus; Reitmeir, Peter; Bethke, Thomas D. (Arzneimittelforschung, 2010)
A randomized, double-blind, 2-way crossover trial of 24 healthy volunteers investigated the influence of esomeprazole (CAS 119141-88-7) and pantoprazole (CAS 102625-70-7), both 1 × 40 mg orally for 11 days, on the pharmacokinetics and pharmacodynamics of diazepam (CAS 439-14-5). Single-dose intravenous diazepam 0.1 mg/kg was administered on day 6. Blood sampling for pharmacokinetic assessment was conducted 0–120 h post diazepam application and data were analyzed using a model-independent approach and ANOVA. Pharmacodynamic parameters were assessed by an oculodynamic test and auditory evoked potentials 0–10 h post diazepam application. Data were analyzed using a linear mixed regression model. The AUC of diazepam was increased by 28.0%, Cmax by 31.4% and t1/2 by 41.1% in the esomeprazole vs. pantoprazole group. Myogenic parameters such as angular velocity of saccadic eye movements and complex choice reaction time were impaired with esomeprazole when compared to pantoprazole after diazepam administration (P < 0.0028) at 4–6 h. The sedation parameter micro-sleep doubled (2.6 vs. 1.1%; P < 0.0073). No differences in auditory evoked potentials were observed. In conclusion, it cannot be ruled out that a relevant pharmacodynamic interaction between diazepam and esomeprazole may occur when both drugs are concomitantly administered. Pantoprazole may provide a higher safety profile.
Keywords: Benzodiazepines; Diazepam; Esomeprazole; Pantoprazole; Pharmacodynamics; Pharmacokinetics; Proton pump inhibitors